The Influence of Teaching Situations and Motivational Beliefs on Teaching Quality Ranking - Supeno (STAI At-Tahdzib, 2025)
Ratings conducted by students are usually used to evaluate the class process.Research shows that ratings are not only based on objective situational characteristics, but also reflect the characteristics of the assessor. This study uses data from1.745 undergraduate students of Prince Diponegoro University Nganjuk for the last 5 years.The study used single trait-multistate model analysis to unravel the variants of instructional quality (student support, cognitive activation). The relationship between motivational beliefs and the component that was also estimated to be consistent across the rankings was the effect of people. The ranking of teaching quality over time is consistent in the same lecture. Consistency is lower when teaching quality ratings are assessed in various lectures. Consistency is higher in lectures that are considered difficult by students than lectures that are considered important. Students who reported higher expectations for success and interest in lectures also rated instructional quality more positively in all teaching situations. The findings of the study show that the ranking of teaching quality is located and shaped by the characteristics of lectures.